Leukocyte adhesion defect: A rare cause of immunodeficiency - Chowdhary, Sona; Kumar, Mohitesh (Indian Journal of Child Health, 2014)
Leukocyte adhesion deficiency 1 (LAD-1) is a rare autosomal recessive disorder of leukocyte function due to integrin deficiency. It is characterized by recurrent bacterial and fungal infections and depressed inflammatory responses despite striking blood neutrophilia. Severe LAD usually presents early in infancy. Here, we report a case who presented late with symptoms of LAD-1 when compared with earlier reported cases and without the usually associated infections.